Just shy of ordinary - Sass, A. J. (Little, Brown and Company, 2024)
Shai, a thirteen-year-old nonbinary homeschooler, attempts to find a "new normal" post-pandemic as they start public school, meet new friends, and learn about their Jewish identity.